Association of immune evasion in myeloid sarcomas with disease manifestation and patients’ survival - Marcus Bauer; Astrid Monecke; Hubert Hackl; Andreas Wilfer; Andreas Wilfer; Nadja Jaekel; Hendrik Bläker; Haifa Kathrin Al-Ali; Haifa Kathrin Al-Ali; Barbara Seliger; Barbara Seliger; Barbara Seliger; et al. (Frontiers in Immunology, 2024)
IntroductionMyeloid sarcomas (MS) comprise rare extramedullary manifestations of myeloid neoplasms with poor patients’ outcome. While the clinical relevance of the tumor microenvironment (TME) is well established in many malignancies, there exists limited information in MS. MethodsThe expression of the human leukocyte antigen class I (HLA-I) antigens, HLA-I antigen processing and presenting machinery (APM) components and the composition of the TME of 45 MS and paired bone marrow (BM) samples from two independent cohorts were assessed by immunohistochemistry, multispectral imaging, and RNA sequencing (RNAseq).ResultsA significant downregulation of the HLA-I heavy chain (HC; 67.5%) and ß2-microglobulin (ß2M; 64.8%), but an upregulation of HLA-G was found in MS compared to BM samples, which was confirmed in a publicly available dataset. Moreover, MS tumors showed a predominantly immune cell excluded TME with decreased numbers of tissue infiltrating lymphocytes (TILs) (9.5%) compared to paired BM (22.9%). RNAseq analysis of a subset of 10 MS patients with preserved and reduced HLA-I HC expression revealed 150 differentially expressed genes and a significantly reduced expression of inflammatory response genes was found in samples with preserved HLA-I expression. Furthermore, low HLA-I expression and low TIL numbers in the TME of MS cases were linked to an inferior patients’ outcome.DiscussionThis study demonstrated a high prevalence of immune escape strategies in the pathogenesis and extramedullary spread of MS, which was also found in patients without evidence of any BM pathology, which yields the rational for the development of novel individually tailored therapies for MS patients.